PENGARUH REKAYASA PENGAIRAN TERHADAP PRODUKTIVITAS BUDIDAYA PADI (ORYZA SATIVA) SAWAH - Raflen Aril Gerungan; Mecky Christofel Telis Pandelaki (LPPM Universitas Terbuka, 2020)
Rice farming always experiences water shortages in dry season which result in low productivity. In order to overcome this problem, efforts are needed in the form of irrigation technology (intermittent and water-saturated condition). The aims of this study is to determine the effect of intermittent irrigation and water-saturated condition irrigation on the production of rice plants. This study used a randomized block design (RCBD) as an environmental design with a split plot design. This study was conducted by making a plot of 4 x 6 meters, totaling to 24 plots. Between every two plots, there is a waterway 50 centimeters wide. Each plot has a waterway for water intake and discharge. Intermittent irrigation treatment was conducted by flooding the plots by water as high as 5 centimeters 3 times at 0–9 HST, 15–29 HST, 35–70 HST, and water drying was also carried out three times at 9–15 HST, 29–35 HST, and 70–80 HST. Water-saturated condition irrigation treatment was conducted by leaving the plots in a state of water saturation without any stagnant water from 0 HST until the production phase. During the treatment of intermittent and water-saturated condition irrigation, fertilizer had been given at a dose of 600 kg/ha, 800 kg/ha, 1.000 kg/ha and 1.200 kg/ha. The parameters observed in this study were the number of active tillers, the number of ears per panicle, the weight of a thousand grains, and the weight of the saplings. The results showed that intermittent and water-saturated condition irrigation did not have a significantly different effect on each parameter of rice production. The highest dry weight production both in intermittent and water-saturated condition irrigation was found in the plot with 1.200 kg/ha fertilizer and the lowest dry weight production was from the plot with 600 kg/ha fertilizer. Kegiatan pertanian padi sawah selalu mengalami kendala kekurangan air di musim kemarau yang berdampak pada produktivitas yang rendah. Guna mengatasi masalah ini maka diperlukan upaya berupa rekayasa pengairan. Tujuan penelitian ini untuk mengetahui pengaruh rekayasa pengairan berselang dan macak-macak terhadap hasil produksi padi sawah. Penelitian ini menggunakan rancangan acak kelompok (RAK) sebagai rancangan lingkungan dengan rancangan perlakuan petak terbagi (split splot). Penelitian dilakukan dengan membuat petakan sebesar 4 x 6 m berjumlah 24 petak. Di antara petakan terdapat saluran air dengan lebar 50 cm. Setiap petak dibuat pintu untuk pemasukan dan pengeluaran air. Perlakuan pengairan berselang dilakukan dengan cara petak digenangi air setinggi 5 cm yang dilakukan sebanyak 3 kali pada 0–9HST, 15–29 HST, 35–70 HST, dan pengeringan air yang juga dilakukan sebanyak tiga kali yaitu pada 9–15 HST, 29–35 HST, dan 70–80 HST. Perlakuan pengairan macak-macak dilakukan dengan membuat petak percobaan selalu dalam keadaan jenuh air tanpa ada air yang tergenang mulai dari 0 HST hingga fase produksi. Pada perlakuan pengairan berselang dan macak-macak, juga diberi pupuk dengan dosis 600 kg/ha, 800 kg/ha, 1.000 kg/ha dan 1.200 kg/ha. Parameter yang diamati pada penelitian ini adalah jumlah anakan aktif, jumlah bulir per malai, berat seribu butir, dan berat ubinan.Hasil penelitian menunjukan rekayasa pengairan berselang dan macak-macak tidak memberikan pengaruh yang berbeda nyata pada setiap parameter produksi padi. Produksi berat kering panen tertinggi baik pada pengairan berselang maupun macak-macak terdapat pada petak yang diberi pupuk 1.200 kg/ha dan produksi berat kering terendah terdapat pada petak yang diberi pupuk 600 kg/ha.